Displacement based finite elements for acoustic fluid–structure interaction (2007)
This paper compares two finite elements formulations used for solving fluid structure interaction problems in acoustics. In this case the displacement is used as variable for representing the behavior of the acoustic fluid. Finite element codes are writing for each formulation and typical fluid structure interaction problems are solved. The results obtained with each formulation are compared and advantages and disadvantages are obtained.